Cervicofacial necrotizing fasciitis caused by Haemophilus influenzae serotype e in a patient with Sjogren's syndrome, systemic lupus erythematosus and hypocomplementaemia. Issue 4 (August 2015) - Azar, Marwan M.; Folk, David; Henderson, Triona; Mehra, Saral; Vining, Eugenia; Banach, David B.
Abstract : Introduction: Haemophilus influenzae has the potential to lead to invasive disease including necrotizing fasciitis, especially in immunocompromised individuals. There are only eight previous reports of monomicrobial necrotizing fasciitis due to this organism, and, to the best of our knowledge, none of the head and neck. There is also limited epidemiological and clinical data on infections caused by non-b serotypes of H. influenzae, including serotype e. Case presentation: A 60-year-old female, with systemic lupus erythematosus, Sjogren's syndrome and hypocomplementaemia, presented with rapidly progressive right-sided facial and neck pain, swelling and erythema. She was treated initially with broad-spectrum antibiotics and underwent emergent debridement of the infected tissues. Intraoperative cultures and blood cultures grew H. influenzae . She required two additional debridements and was treated with ceftriaxone for 3 weeks with resolution of her symptoms. Conclusion: Here, we present the first reported case, to the best of our knowledge, of cervical necrotizing fasciitis due to H. influenzae serotype e. This case highlights the continued clinical importance of H. influenzae as a cause of invasive disease, including necrotizing fasciitis, particularly in immunocompromised individuals. Moreover, the case provides an example of invasive H. influenzae infection caused by a non-b serotype, an emerging concern in the era of widespread H. influenzae serotype b vaccination.